Performance Analysis of IIR and FIR Filters for 5G Wireless Networks - MUHAMMAD RAZEE, AKRAM; Dziyauddin, Rudzidatul Akmam; Azmi, Marwan Hadri; Sadon, Sajaa Kh (International Journal of Integrated Engineering, 2018)
This paper analyses the performances of the Infinite Impulse Response (IIR) and Finite Impulse Response (FIR) filters. By studying the relationship between filter responses with filter orders and delay, the goal is to choose feasible filters that can accommodate more carriers in a bandwidth thus, the spectral efficiency can be increased. For IIR filtering, we employ filters namely Butterworth, Chebyshev, and Elliptic, while the Equiripple, Bohman, and Hamming are studied for FIR filtering. We evaluate these filters in terms of magnitude response, phase response and group delay, and identify the minimum filter order that characterized nearly to an ideal filter response. The results show that the IIR filter has a steep transition region when compared to the FIR filters under the similar order. Our performance analysis showed that the IIR filters, with similar filter order of FIR filters, have also the fastest roll-off, small transition region, and low implementation cost. On the other hand, the FIR filters have linear phase response that related to group delay. Finally, our analysis concluded that Elliptic able to suppress the sidelobes with a minimum order of 10th and Equiripple have the fastest roll-off and narrowest transition region compare to other tested FIR filter. Thus, make these two types of filter feasible candidates to be implemented in 5G wireless networks.